Efektivitas Metode Think Pair Share dan Think Talk Write terhadap Berpikir Kritis - Putri, Dita Amelia; Hermawan, Yoni (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2025)
Students and lecturer activity have an important role in achieving the objectives of learning. In fact, many students are tired of learning in classes that it causes the student’s critical thinking ability to have discussions. Efforts to enhance the critical thinking ability in learning process include implementing the Think Pair Share and Think Talk Write.The objectivesof this research are to know: 1) Enhance critical thinking ability by using the Think Pair Share Method on Pretest and Posttest; 2) Enhance critical thinking ability by using the Think Talk Write Methodon Pretest and Posttest; 3) Difference in critical thinking ability between Think Paire Share Method and Think Talk Write method.Research Method with a quasi experiment. Data analysis techniques involve t-test and N-Gain test. The research finding indicate that: 1) There is a difference in critical thinking ability when using Think Pair Share Method; 2) There is difference in critical thinking ability when using Think Talk Write Method; 3) Critical Thinking Ability difference between Think Pair Share method and Think Talk Write Method.